Renfrew County Virtual Triage and Assessment Centre, March 2024 - An overview of clinical output. - St-Amant, Antoine; Fitzsimon, Jonathan (Université d'Ottawa | University of Ottawa, 2024)
The Renfrew County Virtual Triage and Assessment Centre (VTAC) was established in March 2020. It provides support from medical receptionists, family physicians, and community paramedics 24 hours a day, 7 days a week. VTAC offers various visit modalities, including virtual care by family physicians, in-person care from family physicians and community paramedics, care at Clinical Assessment Centres (CACs) across Renfrew County, and home care for vulnerable, housebound residents. Appointments through VTAC fall into three categories: in-person, virtual and hybrid (which involves real time collaboration between a paramedic in-person with the patient and a physician working remotely). This report briefly presents some of the key metrics for VTAC up to January 31, 2024. The report provides an overview of VTAC’s output, as well as insight into patient demographics, visit modalities, reasons for visits, and visit outcomes. This report mainly focuses on data since VTAC’s inception, with an additional focus since January 2023, as this is when more granular data became available. Granular visit modality data are presented from June 2023. Key Points • Since 2020, VTAC’s clinical focus has shifted from a significant proportion ofCOVID-19 related tests and assessments, to being almost entirely related to other concerns commonly encountered primary care providers. • Over time, the proportion of unattached VTAC patients has increased, with 73% of clinical assessments in 2023 involving unattached residents. • The demand for VTAC services continues to increase, with 2023 marking the highest number of clinical assessments in any year.
Keywords: VTAC; Primary Care; Virtual Care; Hybrid Care; Family Physician; Community Paramedic; Attachment